María Jesús Alvarado Rivera en Buenos Aires: transnacionalidad, ficción sentimental y cultura masiva para un nuevo feminismo - María Vicens (Les Cahiers ALHIM)
This article deals with the years of residence of the Peruvian writer María Jesús Alvarado Rivera in Argentina to analyze how the experience of exile influenced her authorial career, her way of conceiving fiction and her strategies to connect with a mass audience from a popular and feminist perspective. Although the data recovered about this period of her life is scarce, the literary works that frame that transnational experience trace various filiations, both with the Peruvian writers who had settled in fin-de-siècle Buenos Aires, and with the modernization process that the Argentine cultural field went through in the twenties, which give new meaning to those years of migration in a literary key.